Systemic inflammation is a risk factor for oral health: an analysis of data from the UK Biobank - Berger, Martin; Kern, Jaana-Sophia; Schulze-Späte, Ulrike; Wolfart, Stefan; Jankowski, Joachim; Wolf, Michael; Marx, Nikolaus; Marx-Schütt, Katharina (Frontiers in Immunology, 2026)
BackgroundOral health has been implicated as a contributor to systemic inflammation and cardiovascular disease. However, the reverse relationship—whether systemic inflammation causally affects oral health—remains poorly defined. This study investigates the directional role of systemic inflammation in oral disease using genetic and phenotypic data from the UK Biobank.MethodsWe analyzed data from 468,460 UK Biobank participants, integrating self-reported oral health measures with plasma levels of high-sensitivity C-reactive protein (hsCRP). To assess causality, we examined the IL6R single nucleotide polymorphism rs2228145 (p.Asp358Ala), a well-characterized variant associated with impaired IL-6 receptor signaling and reduced systemic inflammation.ResultsHigher hsCRP tertiles were significantly associated with increased prevalence of poor oral health indicators, including tooth loss, dentures, bleeding gums, and loose teeth (all p < 0.001). Carriers of the IL6R C/C genotype exhibited significantly lower hsCRP levels and a reduced burden of oral pathology, including lower odds for toothache (OR 0.91 [95%CI 0.87-0.94]), bleeding gums (OR 0.97 [95%CI 0.94-0.99]), and loose teeth (OR 0.92 [95%CI 0.88-0.96]).ConclusionOur findings support systemic inflammation—mediated via IL-6 signaling—as a causal determinant of impaired oral health. This study provides novel evidence for a directional link from systemic inflammation to oral disease, with potential implications for targeted immunomodulatory interventions in oral health.